2022
DOI: 10.1186/s12876-022-02365-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of incompletely resected small rectal neuroendocrine tumor using endoscope without additional treatment

Abstract: Background In recent years, the incidence of rectal neuroendocrine tumors (NET)s has markedly increased due to the widespread use of screening colonoscopy. However, many patients are referred from local clinics after undergoing conventional endoscopic mucosal resection (EMR) for polyps without perceived NET, with a pathological report of incomplete resection. We evaluated the prognosis of incompletely resected small rectal NET without additional endoscopic resection for small rectal NET less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The incidence of RNETs has rapidly increased over the past few years along with the increase in screening by colonoscopy [ 18–20 ]. However, the CR rates of RNETs treated by endoscopy varied widely as reported by different studies, ranging from 39% to 85% [ 8 , 11 , 16 , 21 ]. The overall CR rate of RNETs is reportedly only 84.08% even after the advanced endoscopic technique of ESD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of RNETs has rapidly increased over the past few years along with the increase in screening by colonoscopy [ 18–20 ]. However, the CR rates of RNETs treated by endoscopy varied widely as reported by different studies, ranging from 39% to 85% [ 8 , 11 , 16 , 21 ]. The overall CR rate of RNETs is reportedly only 84.08% even after the advanced endoscopic technique of ESD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, a large proportion of patients with IR lesions refused salvage treatment for fear of salvage-therapy-related complications and economic burden. It has been reported that 72.7% (56 of 77) of those with incompletely resected small RNETs refused salvage treatment [ 16 ]. For such small IR lesions without additional therapy, it was still unclear whether regular follow-up is safe and feasible.…”
Section: Introductionmentioning
confidence: 99%
“…[54,55] In another study of 77 G1 NET patients with positive surgical margins, 31 patients did not receive additional treatment and did not develop recurrence. [56]…”
Section: Methodsmentioning
confidence: 99%
“…In another study of 77 G1 NET patients with positive surgical margins, 31 patients did not receive additional treatment and did not develop recurrence. [56] Japanese guidelines recommend additional local excision for positive margins after endoscopic resection, even for NET G1 < 1 cm. [8] In Europe and the United States, additional treatment is recommended when invasion of the muscular propria layer is observed or when G2 NET is observed.…”
Section: Guidelinesmentioning
confidence: 99%
“…49 Some units would recommend a watch-and-wait policy but there is a small risk of recurrence and the patient will need long term follow-up. There are large series from South Korea 60,61 where this disease is very common, and it seems clear that up to 2 years the recurrence rate is close to 0. This does not necessarily mean that the recurrence rate is 0 for ever and if watch and wait is adopted we recommend flexible sigmoidoscopy at F I G U R E 1 Diagnostic and therapeutic algorithm for patients with rectal neuroendocrine tumours (NET).…”
Section: Introductionmentioning
confidence: 99%